Application of Fly Ash to Improve Workability, Heat Generation, Autogenous Shrinkage, and Cost-Effectiveness of High Strength Concrete - An Pham-Hoai; Parnthep Julnipitawong; Somnuk Tangtermsirikul; Yusuke Ishii (Science & Technology Asia, 2024)
This study aims to evaluate the full potential of using FA in high strength concrete (HSC) mixtures for relieving the troublesomeness in use of HSC by comparing HSC containing FA with HSC containing silica fume (SF) only and ternary binder HSC containing SF and ground granulated blast furnace slag (GGBS) based on equivalent high strength of 83 MPa and high slump flow of 650mm. In the study, workability, compressive strength, autogenous shrinkage, temperature rise, chloride penetration, and carbonation resistance were tested on nine HSC mixtures with and without FA. Test results reveal that using FA in HSC mixtures reduces their viscosity, particularly in the ternary binder mixtures containing 20% FA and 10% SF. Combining 20% FA with 7% SF in the HSC reduces the maximum temperature measured by the semi-adiabatic temperature rise test. The maximum temperature is equivalent to the HSC mixture with 20% FA or mixture with 30% GGBS and 7% SF in combination. Ternary binder concrete mixtures comprising 20% FA and SF show slightly lower 28-day compressive strength than the SF-only mixtures, but their 91-day compressive strength values are equivalent to those of the SF-only mixtures. Due to the improved microstructures, all HSC mixtures perform well in carbonation and rapid chloride permeability, particularly the ternary binders. In the ternary binder HSC mixtures, although 30% GGBS performs better than 20% FA in terms of compressive strength, utilizing FA in HSC improves concrete performances in terms of viscosity, autogenous shrinkage, heat generation, and rapid chloride permeability as well as cost-effectiveness.